An Investigation into Reading Strategies Employed by Students for Comprehending Exposition Texts - Fatahillah, Muhammad; Nazar, M.; Nisrina, Nisrina (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2023)
This research aimed at identifying the types of reading strategies students employ to absorb exposition text. This study employed a qualitative descriptive approach. The research focused on eleventh-grade students at SMA Negeri 1 Lhokseumwe. Using the snowball nonprobability technique, the researcher selected eight students or respondents as research subjects. Data collecting procedures were surveys and interviews. The data analysis technique used data condensation, data display, and data verification/conclusion. According to an analysis of eleventh-grade students' reading comprehension statistics, problem-solving reading strategies were most frequently utilized to comprehend expository content. Students in the eleventh grade at SMA Negeri 1 Lhokseumawe utilized the problem-solving reading strategy to comprehend the expository text.